STUDENTS’ PERCEPTIONS TOWARD THE EFFECTIVENESS OF COLLABORATIVE BRAINSTORMING IN ACADEMIC WRITING CLASSES - Rendhi Rakasiwi; Listyani - Listyani (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2020)
The 21st century skills include collaboration and teamwork, creativity and imagination, critical thinking, and problem solving. In writing classes collaborative brainstorming is one of many activities that can be conducted by teachers to help students develop their 21st century skills. It is because collaborative brainstorming makes students think critically and creatively, work better in groups, and solve problems collaboratively. This study investigated students’ perceptions on the use of collaborative brainstorming in an academic writing class and its effectiveness in the students’ eyes in writing. The participants of this study were thirty-three English Language Education Program (ELEP) students who were taking Academic Writing class. The data were analyzed qualitatively, supported by open ended questionnaires and semi-structured interviews. The results of the data analysis exposed to prove that collaborative brainstorming helps students in academic writing projects. Finally, this study indicates the importance of classroom interaction during classroom learning activities. This study also suggests a strategy to overcome students’ minor participation during group discussions.